PENERAPAN STRATEGI PEMBELAJARAN GROUP TO GROUP EXCHANGE (GGE) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BAHASA INDONESIA PADA MATERI CERPEN SISWA KELAS XI IPA.1 SMA NEGERI 1 RAMBAH - Rusni Rusni (STKIP ROKANIA, 2021)
Activities and learning outcomes of Indonesian students in class XI IPA.1 SMA Negeri 1 Rambah have not been satisfactory. For this reason, efforts are needed to increase students' Indonesian learning activities and outcomes by applying the Group to Group Exchange (GGE) learning method. The purpose of this study was to explain the process of improving students' Indonesian learning outcomes in short stories material in class XI IPA.1 SMA Negeri 1 Rambah, Rokan Hulu Regency with the Group to Group Exchange (GGE) learning method. The type of this research is classroom action research (PTK). on short story material. The subjects of this study were students of class XI IPA.1 SMA Negeri 1 Rambah. This study consisted of two cycles, each cycle consisting of planning, implementation, observation and reflection. The research instrument was in the form of student activity observation sheets, and learning outcomes test sheets. The data were analyzed with descriptive statistics to see the improvement in student learning outcomes. The results showed that the Group to Group Exchange (GGE) learning method could improve student learning outcomes. The increase in student learning outcomes can be seen from the students' learning completeness in the first cycle, which is 75.00% in the second cycle, increasing to 81.25%. The conclusion of this study is that the Group to Group Exchange (GGE) learning method can improve students' Indonesian learning outcomes on short story material in class XI IPA.1 SMA Negeri 1 Rambah.